Autoestima y rendimiento escolar en niños de la unidad educativa “Carlos Cisneros” de Riobamba, periodo marzo-agosto 2016. - Salgado Tobar, María José (2018)
This investigation was carried out in the Educational Unit "Carlos Cisneros" from Riobamba. The proposal established the influence of self-esteem on each student's school performance. The research is field, bibliographic, cross-sectional, non-experimental, quantitative and descriptive. The population consisted of 162 children, with a sample of 159 children, is non-probabilistic, selected according to inclusion and exclusion criteria. For the collection of data, the Stanley Coopersmith Self-Esteem Inventory (self-esteem levels) was applied, and the qualitative scale of school performance (performance levels) and the outcomes obtained were: 54% corresponds to 86 students with a high average of self-esteem; 66 of these achieved the expected learnings and 20 have proficiency in the expected learnings; 26% corresponding to 41 students have a high level of self-esteem; 23 of these achieved the expected learnings, and 18 have proficiency in the expected learnings; 6% belong to 9 students with a low average of self-esteem that achieve the required learning; 4% corresponds to 7 students with low self-esteem, 6 of these achieved the required learning and 1 is close to achieving the required learning.